Pendidikan Rasa Al-Ghazali: “Gak Cuma Pintar, Hati Juga Kena!” - Fhina Ardini; Niesa Amalia; Herlini Puspika Sari (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This research responds to the contemporary educational crisis dominated by cognitive intelligence ('aql) resulting in the phenomenon of